Back Cover: A Multispectroscopic Study of 3 d Orbitals in Cobalt Carboxylates: The High Sensitivity of 2p3d Resonant X‐ray Emission Spectroscopy to the Ligand Field (Angew. Chem. Int. Ed. 4/2013). Issue 4 (2nd January 2013) - van Schooneveld, Matti M.; Gosselink, Robert W.; Eggenhuisen, Tamara M.; Al Samarai, Mustafa; Monney, Claude; Zhou, Kejin J.; Schmitt, Thorsten; de Groot, Frank M. F.
<x xml:space="preserve">Abstract</x> 3d transition‐metal‐ion coordination is crucial in many chemical processes and in the understanding of their reaction mechanisms. In their Communication on page 1170 ff. M. M. van Schooneveld, F. M. F. de Groot et al. show for cobalt(II) carboxylates that synchrotron‐based 2p3d resonant X‐ray emission spectroscopy (RXES) allows for a far more judicious determination of the metal‐ion coordination environment than benchmark ultraviolet/visible (UV/Vis) and 2p X‐ray absorption (XAS) spectroscopy do.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>